2012
DOI: 10.1097/brs.0b013e318231bb81
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Cervical Pedicle Screw Insertion in Children

Abstract: Safe insertion of cervical pedicle screws is possible in children. Iso-C navigation provides real-time virtual imaging and improves the safety and accuracy of successful pedicle fixation even in altered vertebral anatomy. Pedicle width morphometrics do not restrict screw insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 20 publications
0
16
0
2
Order By: Relevance
“…Traditional wiring techniques are biomechanically inferior to screw-based techniques, and immobilization after surgery may be more difficult for pediatric patients 8 , 12 , 19 , 21) Therefore, the anatomical dimensions of the whole cervical spine must be investigated to study the safety of screw fixation. The suggested minimum thickness needed to allow safe placement of a screw varies in the literature 4 , 5 , 18 , 23) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional wiring techniques are biomechanically inferior to screw-based techniques, and immobilization after surgery may be more difficult for pediatric patients 8 , 12 , 19 , 21) Therefore, the anatomical dimensions of the whole cervical spine must be investigated to study the safety of screw fixation. The suggested minimum thickness needed to allow safe placement of a screw varies in the literature 4 , 5 , 18 , 23) .…”
Section: Discussionmentioning
confidence: 99%
“…After Abumi et al 1) first reported the clinical results of pedicle screw fixation for the subaxial cervical spine, many clinical applications have been executed in adult patients. Recently, Rajasekaran et al 23) reported that safe insertion of pedicle screw is possible in pediatric patients. Vara and Thompson 25) performed a cadaveric study of pediatric cervical pedicle width [mean value : 3.63 mm (C3), 3.73 mm (C4), 4.10 mm (C5), 4.58 mm (C6), 5.15 mm (C7)] with results similar ours.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Though, uncommon studies have been undertaken regarding the use of pedicle screws in preadolescent patients. [11131920212223] Ranade et al . [19] described the accuracy of pedicle screw placement in 16 children aged less than 8 years of age as assessed by CT and reported an overall breach rate of 6.8% with no neurologic or vascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…КТ-морфометрия С 2 позвонка показала, что транспедикулярное проведение винтов размером от 3,5 на 14,0 мм в С 2 возможно у 40-70 % детей старше 2 лет [10,29], при этом ширина и высота ножки примерно одинаковы. В клинической практике транспедикулярная и интерартикулярная фиксация С 2 продемонстрировали надежность и безопасность при использовании у детей [8,13,14,17,23,26,27,37,43,46].…”
unclassified
“…Транспедикулярная фиксация С 3 -С 6 винтами диаметром 3,5 мм и более ограничена высотой ножки и возможна менее чем у трети детей [29,48], но при этом имеется успешный опыт транспедикулярной фиксации С 3 -С 6 винтами диаметром 3 мм у детей старше 6 лет [37]. Мы не используем данный метод фиксации на уровне С 3 -С 6 у детей.…”
unclassified